Initial Teacher Education in the Digital Age: Reflective Practice, Situated Learning and Artificial Intelligence - Sereño Ahumada, Francisco (2024)
Teacher training must adapt to prepare new generations in a constantly changing society. This essay proposes a humanistic approach, exploring how reflective practice, situated learning, and artificial intelligence (AI) can be integrated into teacher training, promoting a modern, effective, and human-centered education. Reflective practice is key to the professional development of teachers, enriching them through dialogue and collaboration. Artificial intelligence, despite its challenges, offers great potential for personalizing learning. Teachers must develop digital skills and a reflective attitude to integrate AI in a critical and responsible manner. Education must strive to build a more inclusive world with equity and social justice, providing opportunities for all students to develop their potential. In this sense, critical reflection and technology, at the service of humans, can contribute to this ideal. This essay invites us to reimagine teacher training, where technology and critical reflection intertwine to enhance the integral development of educators and students, building an education that responds to the challenges of the 21st century and trains conscious and responsible citizens.